H19 non-coding RNA in urine cells detects urothelial carcinoma: a pilot study. (3rd October 2017) - Gielchinsky, Ilan; Gilon, Michal; Abu-lail, Rasha; Matouk, Imad; Hochberg, Avraham; Gofrit, Ofer N.; Ben-Dov, Iddo Z.
Abstract: Context: Urothelial carcinoma (UC) is common and highly recurrent. Diagnosis and follow-up involve invasive cystoscopies. Objective: To evaluate H19 RNA in urine cells as diagnostic tool for UC. Materials and methods: RT-PCR analysis of urine samples from healthy volunteers and UC patients. Results: H19 RNA was unequivocally detected in the urine of 90.5% of patients and 25.9% of controls. H19 copies were three orders of magnitude higher in patients. Receiver operating characteristic analysis showed an area under the curve of 0.933. Conclusions: This pilot study shows that urinary cell H19 is a highly sensitive test for UC and pending verification could transform patient management.